1992
DOI: 10.4319/lo.1992.37.1.0162
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus limitation of primary production in Florida Bay: Evidence from C:N:P ratios of the dominant seagrass Thalassia testudinum

Abstract: Florida Bay is a shallow, seagrass‐dominated embayment on the southern tip of Florida. Variation of C, N, and P content of leaves of Thalassia testudinum was measured on two spatial scales: locally (10–100 m) in relation to a point source of nutrients associated with a bird colony in eastern Florida Bay and regionally (10– 100 km) across all of the bay. Locally, the P content of leaves decreased from a high of 0.16% P (wt/wt) 30 m from the nutrient source to a low of 0.08% 120 m from the source; the C and N co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
240
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 364 publications
(262 citation statements)
references
References 11 publications
14
240
2
Order By: Relevance
“…Lapointe & Clark 1992, Boesch et al 1993, Zieman et al 1999. Whereas the eastern bay region is generally considered to be severely phosphorus-limited (Fourqurean et al 1992, Hitchcock et al 1998, Lavrentyev et al 1998, the central bay generally has sufficient total dissolved nitrogen and phosphorus to support such blooms , Fourqurean & Robblee 1999. The sources of these central bay nutrients (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Lapointe & Clark 1992, Boesch et al 1993, Zieman et al 1999. Whereas the eastern bay region is generally considered to be severely phosphorus-limited (Fourqurean et al 1992, Hitchcock et al 1998, Lavrentyev et al 1998, the central bay generally has sufficient total dissolved nitrogen and phosphorus to support such blooms , Fourqurean & Robblee 1999. The sources of these central bay nutrients (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Everglades water that had the 22 highest initial [TOC] may have also had relatively high bacterial densities that may have influenced decay rates and leaf-water column exchanges. FCE-LTER data on bacterial 24 abundance across this region of the southern Everglades and into Florida Bay suggest that 1) bacterial abundances are highest in the mangrove ecotone and during wet season months when 2 runoff from the Everglades is high, and 2) bacterial abundance is lowest in Eastern Florida Bay relative to these Everglades marsh and mangrove sites as well as central and western Florida 4 Bay, where seagrass productivity is considerably higher (Fourqurean, et al 1992; J. Boyer, unpublished data). 6 We did not attempt to quantify the difference in bacterial densities among our source waters.…”
Section: Resultsmentioning
confidence: 99%
“…The upside-down nature of Shark Bay was firmly established when it was first identified as a P-limited marine ecosystem (Smith and Atkinson 1983, 1984, Smith 1984. The similar spatial pattern in C:P stoichiometry of seagrasses of Florida Bay (Fourqurean et al 1992) and Shark Bay (Burkholder et al 2013a) indicate a common coastal source of P, despite large differences in the water budgets of these two systems Fig. 2).…”
Section: Are All Karstic Coastal Systems and Wetlands Biogeochemicallmentioning
confidence: 91%
“…Long-term biogeochemical data have shown that v www.esajournals.org tidal exchange with the coastal ocean (Fourqurean et al 1992) and submarine groundwater discharge (Herbert and Fourqurean 2009) provide the primary supply of the limiting nutrient, phosphorus (P), to the seagrass meadows of Florida Bay. Geochemical tracer studies show that brackish groundwater transports P upstream as seawater intrusion into the coastal aquifer which is accessible to mangrove roots, and thereby promotes production, particularly in the dry season (Swart and Price 2002, Price et al 2006, Stalker et al 2009).…”
Section: Are All Karstic Coastal Systems and Wetlands Biogeochemicallmentioning
confidence: 99%